3D Augmented Reality Marker-based Mobile Apps Design of Face Mask Layer - Nur Amirah Kamaluddin; Murizah Kassim; Hafizoah Kassim (Society of Visual Informatics, 2023)
The outbreak of COVID-19 has spread rapidly across the globe, affecting how people interact, work and experience their daily lifestyles. The face mask is essential to personal protective equipment (PPE) even though COVID-19 is endemic today. A face mask is required to protect humans, and its description is important. Augmented reality is one new attractive technology for distributing information. This research presents a 3D augmented reality mobile application that visualizes a protective face mask and its material layers called 3DAR-FML. It was designed by utilizing 3D marker-based images on an Android smartphone platform. Ten types of protective face masks and each layer were designed in 3D images using Blender Animation and Unity 3D software. Vuforia Engine applications were used to build a personalized mobile Augmented Reality application. This initiative educates society and markets products in interactive ways that allow visualization of the 3D model of various face masks from android phones. Results present that successful mobile apps were developed. A survey shows that 70% of respondents agreed on the design app based on menu interactivity. This app also has been identified as a helper tool for The National Institute for Occupational Safety and Health (NIOSH) agency Malaysia for safety and health apps for the market and public. This product is significant in societies to gain information on face mask characteristics that help to contribute content based on the standard mask in Malaysia.